(untitled) (Research, Society and Development, 2023)
Melasma is a hyperpigmentation disorder, an increase in melanin production that affects the skin. Characterized by the appearance of dark spots visible most often on the face and other photoexposed regions. It is usually caused by exposure to solar radiation, which is not the only factor for its occurrence. Although both sexes can suffer from this dyschromia, it happens more frequently in women, which impairs their appearance and their relationship with the environment in which they live, since the face is the calling card that people have, and it is an element important for the development of interpersonal relationships both in the personal and professional field, compromising self-esteem. Melasma is not a fully understood disorder, since there is still no cure, so, Based on a literature review, this article intends to investigate the possible causes of melasma, identifying the characteristics of each type, as well as understanding how the use of actives and plant extracts used in phytocosmetic formulations can contribute to the treatment and which ones have the more favorable effect to reduce spots, providing a better quality of life. Since there is a growing demand for well-being and health care, relying on the advancement of science for the most diverse clinical and aesthetic conditions. as well as understanding how the use of actives and plant extracts used in phytocosmetic formulations can contribute to the treatment and which ones have the most favorable effect to reduce stains, providing a better quality of life. Since there is a growing demand for well-being and health care, relying on the advancement of science for the most diverse clinical and aesthetic conditions. as well as understanding how the use of actives and plant extracts used in phytocosmetic formulations can contribute to the treatment and which ones have the most favorable effect to reduce stains, providing a better quality of life. Since there is a growing demand for well-being and health care, relying on the advancement of science for the most diverse clinical and aesthetic conditions.